2010
DOI: 10.21896/jksmch.2010.14.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening Behavior and Related Factors among Married Women

Abstract: Objectives: The purpose of this study was done to identify cervical cancer screening behavior and related factors among married women. Methods: This study's subjects were 225 married women who visited two laying-in women's hospitals located in P city in Korea. Data were collected from April 1, 2006 to April 20, 2006 by using a self-reported questionnaires and analyzed descriptive statistics, x 2 -test and logistic regression analysis using SPSS/WIN 12.0 program. Results: 1) Respondents attitude and the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Prior studies in the Korean adult population suggested that the reason for the low cancer screening rates was because people believed they were healthy and asymptomatic (Hwang et al, 2002;Oh et al, 2010). Studies have reported that the factors influencing the cancer screening rate include the intention to receive screening, general health screening, age, education level, regular visits to the doctor and regular exercise (Valentiny et al, 2012;Suh et al, 2013).…”
Section: Factors Affecting Cancer Screening Intention and Behavior Ofmentioning
confidence: 99%
“…Prior studies in the Korean adult population suggested that the reason for the low cancer screening rates was because people believed they were healthy and asymptomatic (Hwang et al, 2002;Oh et al, 2010). Studies have reported that the factors influencing the cancer screening rate include the intention to receive screening, general health screening, age, education level, regular visits to the doctor and regular exercise (Valentiny et al, 2012;Suh et al, 2013).…”
Section: Factors Affecting Cancer Screening Intention and Behavior Ofmentioning
confidence: 99%
“…Cervical cancer prevention education was also effective in improving preventive behaviors against cancers in a study by Perkin (2007), which reported an improvement in preventive behaviors post-education. Oh et al (2010) found that an early cancer screening of married women was related to knowledge about cervical cancer. The scale of cancer prevention behaviors was developed for this study to measure the level of preventive health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study has yet addressed the effectiveness and limitations of the screening test including the accuracy of this test since its introduction in Korea. Only factors influencing program participation including cognitive and behavioral parameters [17,18] have been explored. The effect of the screening test on early detection and prevention of cervical cancer should be reported to encourage more women to participate in the national cancer screening program.…”
Section: Introductionmentioning
confidence: 99%